Communicative Language Teaching Manifestation in an English as a Foreign Language Classroom - Effendi, Dwiky Ahmad; Novita, Dian (Linguistics and ELT Journal, 2024)
The principles of CLT align with the evolving needs of EFL learners. They address the demand for functional language skills that go beyond rote memorization and passive learning. Moreover, as language is generally seen as a tool for communication rather than a set of strict rules, CLT emphasizes interaction, authenticity, and real-world language use within the learning process. Through qualitative research design, the study aims to gain profound insights into the nuances of CLT application within this educational context. The primary participant is an experienced English teacher at an Islamic Elementary School in Sidoarjo, East Java, Indonesia. She was chosen for her extensive background in CLT and teaching experience. The instruments for data collection include classroom observations and semi-structured interviews with the teacher, aiming to understand the challenges, successes, and strategies employed in integrating CLT principles. As a result, CLT integrates mechanical, meaningful, and communicative practices, fostering language proficiency through active engagement in authentic communication scenarios. At the school, CLT methodologies are employed to create dynamic learning experiences tailored to students' needs, nurturing enthusiasm and fluency in English.